Sanidade e caracteres agronômicos de híbridos de milho em função da população de semeadura e da aplicação de fungicidas em duas safras - Maldaner, Henrique (2015)
Seeking to evaluate the major foliar diseases of stem and spike occurring in maize and which interference on yield and grain quality. Influenced by genetic factor of different hybrids and different plant populations. Thus, two experiments were carried out in the first second crop corn (2014/2014) and the second experiment the summer harvest (2014/2015). In both experiments were evaluated two different commercial hybrids with six different plant populations and the practice of using fungicides, conducted in the municipality of Cafelândia, PR. The experimental design was a randomized block design with three replications, in a split sub plots. The portions defined by two commercial corn hybrids, subplots six different populations of sowing and sub subplots with use of fungicide. incidence and severity assessments were carried out and estimated the area under the disease progress curve of the main foliar diseases. also obtained grain yield, grain defective levels and levels of mycotoxins on grain. In both studies it was found that the genetic factor is essential for better grain quality, adjustment of plant population directly affects the yield and the practice of use of fungicides brought improvements to the control of foliar diseases and increase thatch the quality and yield of grain produced.